INFORMATIVE PROVIDING OF THE INNOVATION PARADIGM - Smirnova, Nadiya; Smirnova, Iryna (SWorld-Ger Conference proceedings, 2023)
The work examines information support systems of the innovative paradigm. The essential characteristics of innovative activity have been studied. The place of management in the innovation paradigm is clarified. It was determined that the management proces